Teacher Conduct: A Survey on Professional Ethics among Chinese Kindergarten Teachers - Ji, Zhaolin (International Journal of Learning, Teaching and Educational Research, 2017)
Teacher professional ethics have recently become a much debated issue in China, which is in the wake of China‟s new population policy that ends the ’one-child’ policy after 35 years of stringent enforcement. With increasingly more children enrolled in early childhood services, the quality of the teaching force is to stand a tougher test of public scrutiny. Professional ethics is an integral and pivotal component of teacher quality. Utilizing questionnaire as the data collection method, this study examines self-reported professional conduct of 437 in-service teachers from 50 kindergartens across three provinces of China. It is found that: (1) The majority of the kindergarten teachers report themselves as compliant with the professional ethics when facilitating all the daily routine activities and when working with colleagues and parents; (2) Several ethical issues exist with some kindergarten teachers such as differentiated approach to children from different backgrounds, unawareness of the importance of parents as stakeholders, and unhealthy relationship with colleagues. https://doi.org/10.26803/ijlter.16.9.8